Ausência/presença de artigo definido diante de antropônimos na fala dos moradores de Mariana e Uberaba MG - Braga, Luciene Maria (2012)
We analyze synchronically, within this study, the syntactic variation, absence/presence of the definite article before antroponyms, proper nouns, in the Brazilian Portuguese speakers speech from the towns of Mariana, Uberaba, as well as other towns in the metropolitan area of Belo Horizonte and Triângulo Mineiro (an area triangle shaped in the west of Minas Gerais state bordering the state of São Paulo), respectively. The current research is laid on Labov s (2008) Variationist Sociolinguistic methodological and theoretical conjectures and Parametrical Sociolinguistics of Tarallo e Kato (1989). It was developed from the general hypothesis that Mariana and Uberaba have diverging patterns regarding the use of the definite article before antroponyms. The corpus of the research is composed of 38 oral interviews from which 20 took place in Mariana and 18 in Uberaba. Data obtained from interviews underwent separately a quantitative analysis through the statistics software GOLDVARB/2001. Results show the antroponym factor groups as the speaker s intimacy enumeration and degree item with the referent relevant to the people from Mariana, and the antroponym syntactic function factor in the sentence group as the most relevant to the people from Uberaba. It was attested the hypothesis that the two towns have diverging patterns regarding the variation studied, i.e., the lack of the definite article before the antroponym in Mariana is the preferable structure by its speakers; in Uberaba, on the contrary, the presence of the article is the prevailing structure.